Pengaruh Tingkat Religiusitas dan Gaya Hidup Santri Terhadap Pola Perilaku Konsumen Islam - Dwi Ismi Azizah (An Nahdhoh Jurnal Kajian Islam Aswaja, 2022)
The purpose of this study was to find out how the influence of lifestyle variables and the level of religiosity of the students of the Ainul Yaqin Islamic University Islamic University of Malang on Islamic consumer behavior patterns. This research is a causal associative research. The data collection method uses questionnaires distributed to respondents and interviews. The number of samples (respondents) in this study were 50 students selected by simple random sampling technique. Data analysis using multiple regression statistical models. Data is processed using reliability test, validity test, and regression test. The results of the study in the t test found that both variables had an effect on the consumption behavior of students, known by the simultaneous F test value of 0.002, and the partial T test of religiosity level of 0.005 and lifestyle of 0.013.